+0  
 
0
233
1
avatar
3(y-2)-2(4-2y)+(6-7y)
Guest Mar 1, 2012
 #1
avatar
0
breaking this down we have:
3(y-2)=3y-6
-2(4-2y)=-8+4y
now rewrite the new equation: 3y-6-8+4y+6-7y=-8
3y+4y-7y=0
-6-8+6=-8
Guest Mar 2, 2012

9 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.